Optimizing The Role of Health Cadres In Conducting Education By Using Books on Monitoring High-Risk Pregnant Women During The Pandemi - Desmarnita, Ulti; Hasnani, Fenti (Devotion : Journal of Research and Community Service, 2023)
High-risk pregnancy is a condition of pregnancy that is a factor in the occurrence of danger and severe complications for both the mother and the fetus in the womb and can cause death, illness, disability, discomfort and dissatisfaction. The health of pregnant women can be maintained through health care efforts using antenatal care. These efforts aim to reduce maternal mortality with various interventions according to the problems of pregnant women at risk. Risk factors for pregnant women are proactively introduced or informed by health workers or trained officers in the community, such as health cadres. Health cadres will easily monitor and assist pregnant women at risk if they understand risky pregnancies, especially during the pandemic. For that we need the right media in conveying health information, especially about monitoring high risk pregnant women in the form of books. Objective: to optimize the role of health cadres in conducting education using books. Method: the activity begins with a pretest, inserting material to get to know the contents of the book, and studying the book. Followed by taking cases, concluding the category of at-risk pregnant women by cadres in the Neglasari District, Tangerang City. Results: there was a good understanding of cadres in the pretest 7 people (35%), and an increase in good understanding in the posttest 17 people (85%). The conclusion of education using books can increase the knowledge of cadres about pregnant women at risk during the pandemic. Recommendation: Increased understanding of pregnant women at risk for health cadres can use books, including for health worker or other health services during a pandemic in the community.